Awareness and knowledge of birth defects among antenatal Clinic attendees at the University College Hospital Ibadan, South-West, Nigeria. (2021)
OBJECTIVES: This study assessed the knowledge of risk factors and prevention of birth defects among ante-natal clinic attendees at the University College Hospital, Ibadan, Oyo State, Nigeria METHODS: This was a cross sectional study among 415 mothers who presented at the antenatal clinic, A semi-structured questionnaire was used to obtain information on respondents socio-demographic profile, pregnancy, birth history, knowledge on prevention and risk factors for birth defects. Descriptive statistics was used to present results, independent t-test and ANOVA were used to determine the factors associated with mean of overall knowledge of birth defects. Test statistics was done at a 5% level of statistical significance. RESULTS: The mean age of the women was 31.7 + 4.8 years Overall, 93 (22.4%) of the women were above 35 years, 118 (29.9%%) were skilled workers and 343 (84.9%) had tertiary education. More than half (219, 52.8%) of the respondents had good knowledge of birth defects (56.4%a had good knowledge of prevention and 66.0% had good knowledge of risk factors) Antenatal clinic attendees in their first trimester had higher mean overall knowledge score (8.3 t 4.9) compared to those in second (7.9 + 4.5) and third (7,9 + 4,9) trimesters but this was not statistically significant (p=0.873). However, respondents in skilled/ semi-skilled occupation (8_62) had a significantly higher mean knowledge score compared with those in unskilled occupation/ unemployed (7,33) (p=0.005) CONCLUSION: Knowledge of birth defects is relatively low among women. To reduce the occurrence and severity of birth defects, there is a need to educate mothers on the knowledge, prevention and importance of screening for birth defects.